Pengembangan Media Papan Konsep Perkalian Terhadap Kemampuan Kognitif pada Materi Perkalian Kelas IV di SDN Kelapa Dua - Putri, Salma Anindya; Yandari, Indhira Asih Vivi; Rakhman, Patra Aghtiar (CV. Rayyan Dwi Bharata, 2025)
-